Determinants of "TikTok” addiction among university students / Nor Azilah Husin, Muhamad Saiful Hanif Khairi and Nurul Syazana Mohamad Nazeri - Husin, Nor Azilah; Khairi, Muhamad Saiful Hanif; Mohamad Nazeri, Nurul Syazana (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The younger generation nowadays loves to take pictures or make short videos to post on social media. Tik Tok is a short 15-second video application, made by ByteDance, a Chinese company called Douyin in China. It is made with a system that assists persons in creating and expressing such as lip-sync video. A melody can encourage many people to make short videos. This research is to study the factors that cause short video TikTok application addiction among students. T-test and ANOVA and multiple regression to determine the relevance and significance of the relationship between the selected variables were conducted. This study proved that social factors, family factors, and lifestyle factors are significantly related to the short video TikTok addiction. The test revealed that a variance of 63.4% (R2) of “TikTok" addiction could be explained by the social, family, and lifestyle factors.